Manipulation of rapid eye movement sleep via orexin and GABAA receptor modulators differentially affects fear extinction in mice: effect of stable versus disrupted circadian rhythm. Issue 9 (15th March 2021) - Clark, Jacob W; Daykin, Heather; Metha, Jeremy A; Allocca, Giancarlo; Hoyer, Daniel; Drummond, Sean P A; Jacobson, Laura H
Abstract: Sleep disruption, and especially rapid eye movement (REM) sleep disruption, is associated with fear inhibition impairment in animals and humans. The REM sleep-fear inhibition relationship raises concern for individuals with posttraumatic stress disorder (PTSD), whose sleep disturbance is commonly treated with hypnotics that disrupt and/or decrease REM sleep, such as benzodiazepines or "Z-drugs." Here, we examined the effects of the Z-drug zolpidem, a gamma-aminobutyric acidA (GABAA ) receptor positive allosteric modulator, as well as suvorexant, an orexin receptor antagonist (hypnotics which decrease and increase REM sleep, respectively) in the context of circadian disruption in murine models of fear inhibition-related processes (i.e. fear extinction and safety learning). Adult male C57Bl/6J mice completed fear and safety conditioning before undergoing shifts in the light–dark (LD) cycle or maintaining a consistent LD schedule. Fear extinction and recall of conditioned safety were thereafter tested daily. Immediately prior to the onset of the light phase between testing sessions, mice were treated with zolpidem, suvorexant, or vehicle (methylcellulose). Polysomnographic analyses showed the temporal distribution of REM sleep was misaligned during LD cycle-shifts, while REM sleep duration was preserved. Suvorexant increased REM sleep and improved fear extinction rate, relative to zolpidem, which decreased REM sleep. Survival analysis demonstrated LD shifted mice treated with suvorexant were faster to achieve complete extinction than vehicle and zolpidem-treated mice in the LD shifted condition. By contrast, retention of conditioned safety memory was not influenced by either treatment. This study thus provides preclinical evidence for the potential clinical utility of hypnotics which increase REM sleep for fear extinction after PTSD-relevant sleep disturbance.